2017
DOI: 10.17159/2411-9717/2017/v117n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of ducted fan system variables on ventilation in an empty heading using CFD

Abstract: The effect of some of the system variables in forcing and exhausting ducted fan systems on ventilation in an empty heading was investigated using computational fluid dynamics(CFD) and comparative analyses. The diameter of the duct, duct mouth to face distance, and the power of the fan (quantity delivered by the fan) were varied and their effect on ventilation determined through a comparative analysis of the flow rates calculated close to the face of the heading. Estimation models were developed, which can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…In general terms, it can be observed that the larger the tunnel section and the clean airflow rate, the longer the maximum effective distance. These results are in accordance with Feroze and Genc [29]. Figure 12b shows the transformed data according to the first dimensionless coefficient and the logarithm of the second.…”
Section: Mathematical Model For the Effective Distancesupporting
confidence: 88%
“…In general terms, it can be observed that the larger the tunnel section and the clean airflow rate, the longer the maximum effective distance. These results are in accordance with Feroze and Genc [29]. Figure 12b shows the transformed data according to the first dimensionless coefficient and the logarithm of the second.…”
Section: Mathematical Model For the Effective Distancesupporting
confidence: 88%